2000
DOI: 10.1021/ja994524e
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Discrete Interactions upon Rupture of Au Microcontacts to Self-Assembled Monolayers Terminated with −S(CO)CH3 or −SH

Abstract: Pulloff forces were measured under solvent for Au-coated atomic force microscopy (AFM) tips in contact with -S-acetate-, -O-acetate-, -SH-, or -OH-terminated self-assembled monolayers (SAMs). The SAMs were formed by adsorption of ω-functionalized undecylphosphonic acids on metal oxide substrates. In ethanol and hexadecane, the mean force required to rupture Au/S-acetate microcontacts was 7 times greater than the mean force required to break Au/O-acetate contacts, consistent with the known affinity of S-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 66 publications
3
38
0
Order By: Relevance
“…Although the direct contact of thiol-modified AFM tip with gold substrate can speed up the reaction between the thiol and gold (as compared with the reaction in free solution) due to the shorter mass transport time, normally higher indentation force (4200 pN) will not speed up the reaction further, and indentation force that is too high may even destroy the thiol group or the PEG linker. Considering the fact that the time for mass transport in our AFM experiment is nearly zero, the 3.0 s interaction time necessary for strong interaction is the formation of covalent Au-S bonds 25,55 . However, the reaction time for the formation of SAMs can be different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the direct contact of thiol-modified AFM tip with gold substrate can speed up the reaction between the thiol and gold (as compared with the reaction in free solution) due to the shorter mass transport time, normally higher indentation force (4200 pN) will not speed up the reaction further, and indentation force that is too high may even destroy the thiol group or the PEG linker. Considering the fact that the time for mass transport in our AFM experiment is nearly zero, the 3.0 s interaction time necessary for strong interaction is the formation of covalent Au-S bonds 25,55 . However, the reaction time for the formation of SAMs can be different.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanically controlled breakjunction experiments 32,33 that are slightly different from the AFM-based force experiments have demonstrated that the breaking of the molecular junctions takes place at Au-Au bonds near the molecule-electrode contact and produces a similar rupture force of 1.5 nN. However, an AFM-based force experiment conducted by Skulason et al 25 showed a small force value of 0.1 nN, which was also demonstrated to be the abstraction of thiolate-complexed gold atoms from the tip surface. Recently, Venkataraman et al 34 measured the breaking force in thiol junctions and showed a rupture force of B1.0 nN.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The work of Skulason and Frisbie [388] deals with the adhesion between gold and S-acetate-, Oacetate-, SH-and OH-terminated SAMs in different solvents, and the accent is put on the detection of the discrete rupture forces or force quanta (see also [389]). The authors found a force quantum of 0.1 nN in histograms of the adhesion force and assigned it to the rupture of individual chemical bonds.…”
Section: Determination Of Hamaker Constants Adhesion and Surface Enementioning
confidence: 99%
“…Meanwhile, the binding energy of Cd-S (208.5 ± 20.9 kJ/ mol) is larger than that of Au-S (120 kJ/mol), which also indicates that the Cd(SG) 4 complex is more stable than the Au-SG. 31,32 The spherical shaped (GS) 4 Cd complexes have more net negative charge, thus the (GS) 4 Cd complexes have weaker electrostatic interaction with AuNPs than that of the linear GS-M-SG. Because AuNPs are synthesized by citrate reduction of HAuCl 4 , the surface of AuNPs has negative charges from citrate anions.…”
mentioning
confidence: 99%